Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) IV. The sakaiella species group, with descriptions of fifteen new species - Wang, Shuxia; Jia, Yanyan (Zootaxa, 2019)
The sakaiella species group of the genus Promalactis Meyrick, 1908 is established on the basis of forewing pattern characteristics. Forty-one species are reported, including 15 new species: P. curvitaeniata Wang sp. nov., P. biprocessa Wang sp. nov., P. lvovskyi Wang sp. nov., P. subquadrata Wang sp. nov., P. tibetica Wang sp. nov., P. auremacularis Wang sp. nov., P. apicidigitata Wang sp. nov. P. campanulata Wang sp. nov., P. bicornea Wang sp. nov., P. spiniflagellata Wang sp. nov., P. grandilobata Wang sp. nov., P. arciformis Wang sp. nov., P. bornensis Wang sp. nov., P. cribrata Wang sp. nov. and P. oliviformis Wang sp. nov. Photographs of adults and genitalia of the new species are provided. A checklist of all the species belonging to the sakaiella species group is included, with original citations given to the known species.